HUBUNGAN UMUR DAN PARITAS DENGAN LAMA KALA I PERSALINAN - SITOHANG, TIUR; Ganda Agustina Simbolon; Elny Lorensi Silalahi, (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Childbirth is a complex physiological process that involves regular uterine contractions leading to complete cervical dilation. The duration of the first stage of labor varies greatly among individuals and is influenced by various factors, such as the strength of contractions, fetal position, psychological condition, maternal age, and parity. This study aimed to determine the relationship between maternal age and parity with the duration of the first stage of labor. This research was a quantitative study with a correlational design to analyze the relationship between age, parity, and the duration of the first stage of labor. The sampling technique used in this study was consecutive sampling, in which all subjects who came and met the inclusion criteria were included until the required number of participants was reached. The total sample consisted of 50 respondents. The inclusion criteria were singleton pregnancy, third-trimester gestational age, and the absence of obstetric complications. Most respondents were aged 21–35 years (40 participants), which is considered the healthy reproductive age range. Most respondents were multiparous in the intervention group (36 participants). The majority experienced a labor duration of 2–5 hours (84%). There was a significant relationship between maternal age and the duration of the first stage of labor (p-value = 0.029 < 0.05). There was also a significant relationship between parity and the duration of the first stage of labor (p-value = 0.002). These findings indicate that maternal age and parity are associated with the duration of the first stage of labor.